ANALISIS PELAYANAN TERAPEUTIK TERHADAP KEPATUHAN PASIEN TUBERCULOSIS RESISTEN OBAT DI WiILAYAH KERJA PUKESMAS KOTA MEDAN - Mayang Sari Ayu (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2019)
Abstract Adherence patient in the treatment of second-line tuberculosis is the success of controlling drug resistant tuberculosis. Data from the World Health Organization report (2017) only about 66% of drug-resistant tuberculosis patients follow second-line treatment until recovery. WHO places Indonesia at level eight among countries with high burden with drug-resistant tuberculosis in the world. Objective: Analyze therapeutic service of adherence patient drug resistant tuberculosis treatment. Subjects and Methods: This type of research uses observational analytic cross sectional design, conducted at 3 microscopic referral community health centers in the city of Medan. The sample of the study consisted of 32 patients with total sampling technique. The independent variables were medical services, pharmaceutical services, and nursing services. The dependent variable is adherence patient drug resistant tuberculosis treatment. Sources of research data from primary data through structured interviews and secondary data from a review of the patient's medical record. Data analysis used chi square tests and multiple logistic regression tests with a confidence level of 95%. Results: The analysis shows that all variables have a significant relationship between therapeutic services and adherence patient with drug resistant tuberculosis treatment. Analysis of the variables of medical services (p=0.002), pharmaceutical services (p=0.020), and nursing services (p=0.003) affect the compliance of patients undergoing second-line tuberculosis treatment. Conclusion: Teraupetic service variable had a significant effect on adherence patient drug resistant tuberculosis treatment (p> 0.05). The therapeutic service effort at the community service center is providing easy access to services, overcoming side effects of treatment, active case treatment TB officers and family psychosocial support.Keywords: Therapeutic Services, Drug-Resistant Tuberculosis, Medical Services, Pharmaceutical Services, Nursing Services